Finite element modeling of cerebral aneurysm - Alexson, Abit (2010)
An aneurysm is an abnormal bulging or widening of a portion of an artery due to weakness in the wall of the aortic wall. It happens when the mechanical stress exceeds the tensile strength of the tissue. Nowadays, an accurate decision to predict the rupture of the aneurysm is not is founded yet. This study is focusing on cerebral aneurysm that is occurring at the circle of Willis area. By using the simulation tools, the stress behaviour on cerebral aneurysm (CA) area will be analyzed. As the size of an aneurysm increases, there is a potential of rupture of aneurysm. Studying the mechanical properties in real CA’s can better the research of aneurysm behaviour. This study consists of three cases with the different size of aneurysms which are 2.5 mm and 3.5 mm in radius. The simulation of the model was studied under incompressible, non-Newtonian, viscous, non pulsatile condition in which we investigated computationally in a three-dimensional configuration using a Computational Fluid Dynamics (CFD) program. Currently, the decision to treat a diagnosed, unruptured aneurysm is based primarily on the maximum dimension of the lesion even though there is controversy over the critical size. Our results from finite element analysis reveal important roles of lesion shape, material properties, and loading conditions in governing the distributions of stress within the saccular aneurysms. This research finds that maximum stresses increase markedly with increases in lesion size, the ratio of neck diameter to lesion height, and the pressure.